2020
DOI: 10.1155/2020/2068961
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds of Abnormality Perception in Facial Esthetics among Laypersons and Dental Professionals: Profile Esthetics

Abstract: Aim. To find thresholds at which laypersons and dental professionals from Jordanian population perceive abnormalities in sagittal positioning of upper and lower jaws as a major determinant to facial profile esthetics. Materials and Methods. Using photo editing software, a baseline profile image of a young male was manipulated on a 2 mm incremental basis to move each of the upper and lower jaws backward and forward relative to true vertical line (TVL) at which four variables of maxillary and mandibular retrusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Most of the specialized categories (orthodontists, generic dentists, and maxillofacial surgeons) assessed a sagittal retrusion of the maxilla, but only orthodontists and maxillofacial surgeons recognized that the alteration of the middle facial third is an important component of the skeletal class III malocclusion. These results agree with Alrbata and colleagues who showed that orthodontists are more sensitive in perceiving maxillary retrusion than other categories [13]. Probably, orthodontists pay more attention to maxillary development to intercept a skeletal class III malocclusion already in the early stages of growth [13].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Most of the specialized categories (orthodontists, generic dentists, and maxillofacial surgeons) assessed a sagittal retrusion of the maxilla, but only orthodontists and maxillofacial surgeons recognized that the alteration of the middle facial third is an important component of the skeletal class III malocclusion. These results agree with Alrbata and colleagues who showed that orthodontists are more sensitive in perceiving maxillary retrusion than other categories [13]. Probably, orthodontists pay more attention to maxillary development to intercept a skeletal class III malocclusion already in the early stages of growth [13].…”
Section: Discussionsupporting
confidence: 91%
“…These results agree with Alrbata and colleagues who showed that orthodontists are more sensitive in perceiving maxillary retrusion than other categories [13]. Probably, orthodontists pay more attention to maxillary development to intercept a skeletal class III malocclusion already in the early stages of growth [13]. Furthermore, both orthodontists and maxillofacial surgeons had to conform their aesthetic canons with the new preferences of a more protruded facial profile; therefore, they usually focus on jaw retrusion [15].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Profile esthetics might be perceived differently among various groups (especially laypeople). Some studies have implied that professionals might be biased as a result of their educational background [28], while others have stressed that laypeople might better reflect cultural influence when assessing facial attractiveness [18,37]. Nevertheless, some authors have reported general agreement among professionals and laypeople in terms of perception of facial appearance [3,32].…”
Section: Discussionmentioning
confidence: 99%